2019
DOI: 10.3390/fishes4030048
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Bisphenol A and Tetrabromobisphenol A on Cell Viability and Reproduction-Related Gene Expression in Pituitaries from Sexually Maturing Atlantic Cod (Gadus morhua L.)

Abstract: Bisphenol A (BPA) and tetrabromobisphenol A (TBBPA) are widely used industrial chemicals, ubiquitously present in the environment. While BPA is a well-known endocrine disruptor and able to affect all levels of the teleost reproductive axis, information regarding TBBPA on this subject is very limited. Using primary cultures from Atlantic cod (Gadus morhua), the present study was aimed at investigating potential direct effects of acute (72 h) BPA and TBBPA exposure on cell viability and the expression of reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Based on the results summarized in Figures 1 and 2, we concluded that the optimal protocol was to culture primary pituitary cells from previtellogenic rainbow trout and to expose cell cultures to chemical treatments with or without 3.7 nM (1 ng/mL) E2 for a period of 3 days. These test conditions were influenced by decades of in vitro experiments studying the effects of hormones on pituitary function in salmonids (see Luckenbach et al, 2010; Weil et al, 1986) and are generally consistent with studies examining hormone and EAC effects on primary pituitary cells from other cold water fish species (von Krogh et al, 2019a, 2019b). We found that pituitary cultures from previtellogenic trout were much more responsive to E2 stimulation than cells from vitellogenic trout, suggesting that understanding the hormonal milieu at pituitary collection is critical to the interpretation of primary cell culture results.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Based on the results summarized in Figures 1 and 2, we concluded that the optimal protocol was to culture primary pituitary cells from previtellogenic rainbow trout and to expose cell cultures to chemical treatments with or without 3.7 nM (1 ng/mL) E2 for a period of 3 days. These test conditions were influenced by decades of in vitro experiments studying the effects of hormones on pituitary function in salmonids (see Luckenbach et al, 2010; Weil et al, 1986) and are generally consistent with studies examining hormone and EAC effects on primary pituitary cells from other cold water fish species (von Krogh et al, 2019a, 2019b). We found that pituitary cultures from previtellogenic trout were much more responsive to E2 stimulation than cells from vitellogenic trout, suggesting that understanding the hormonal milieu at pituitary collection is critical to the interpretation of primary cell culture results.…”
Section: Discussionmentioning
confidence: 70%
“…Primary pituitary cell cultures from asynchronous spawning fishes such as the marine medaka ( Oryzias melastigma ) have been used for rapid detection of endocrine‐disrupting activity for several well‐characterized chemicals including E2, 2,2′,4,4′‐tetrabromodiphenyl ether (BDE‐47), and 4‐NP (Tse et al, 2013). A more recent study used pituitary cells prepared from mixed‐sex Atlantic cod ( Gadus morphua , a group‐synchronous spawner) to evaluate bisphenol A (BPA) and tetrabromobisphenol A (TBBPA) effects on Gth expression (von Krogh et al, 2019b). These studies demonstrate the potential of primary pituitary cells as a contaminant screening tool.…”
Section: Introductionmentioning
confidence: 99%
“…The reproductive ability in males can be reduced, as a result of increased concentrations of TBBPA, which can alter the mobility of sperm cells, sperm concentration, displace the lateral head, and angular displacement [ 91 , 92 ]. Loss of sexual desire, low sperm count and erectile disfunction was also noticed in males exposed to TBBPA [ 93 , 94 ].…”
Section: Toxicity Studies and Assessment Of Tbbpa On Humansmentioning
confidence: 99%
“…Brominated phenolic compounds have been released to the environment via the use of brominated flame retardants (BFRs). Some BFRs are phenolic in their native configuration such as tetrabromobisphenol A (TBBPA), which has been shown to alter expression reproductive-relevant genes in fish (von Krogh et al 2019). Other BFRs may be converted to HPCs as a result of metabolism (Hakk and Letcher 2003).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%